2007 International Conference on Mobile Data Management 2007
DOI: 10.1109/mdm.2007.12
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Peer-to-Peer Data Dissemination with Resource Constraints

Abstract: Peer-to-peer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…Wolfson et al [2] suggested there are three resource constraints in mobile P2P: bandwidth, energy, and storage. This means 1) a node with instable wireless bandwidth cannot maintain the quality of the forwarded stream high, while a node with narrow wireless bandwidth can forward the stream at the limited rate; 2) mobile nodes easily disconnect from the service because of running out the batteries and poor wireless channels.…”
Section: Discussion: Remaining Issues In Mobile P2pmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolfson et al [2] suggested there are three resource constraints in mobile P2P: bandwidth, energy, and storage. This means 1) a node with instable wireless bandwidth cannot maintain the quality of the forwarded stream high, while a node with narrow wireless bandwidth can forward the stream at the limited rate; 2) mobile nodes easily disconnect from the service because of running out the batteries and poor wireless channels.…”
Section: Discussion: Remaining Issues In Mobile P2pmentioning
confidence: 99%
“…Particularly, in this paper, we consider how nodes in P2P multicast services will be required to forward data or streams to other nodes. In general, mobile users feel much larger psychological cost due to strict limitations on bandwidth, processing power, memory capacity, and battery life, and they want to minimize their contributions to these services [2]. Therefore, the issue of how we can reduce this psychological cost remains.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying motives are also varied depending on the application domain and individual system requirements and/or constraints. In some domains, the selection of sources might be constrained in certain ways (e.g., cost, energy, timely decisions) [48]. Approaches that operate under resource constraints often resort to the use of a subset of the source population.…”
Section: Related Workmentioning
confidence: 99%
“…peers joining and leaving). Also, techniques have been developed (Wolfson et al, 2007) that explicitly take into account resource constraints like limited energy, communication bandwidth and storage of devices in a mobile ad-hoc environment. For our purpose, we are particular interested in disseminator peers, which take full responsibility for context distribution in this architecture.…”
Section: Architecturementioning
confidence: 99%